FAN_TESTICK Kit: tool to assist students in memorising and understanding chemical tests involving organic compounds / Norleha Binti Mad Dukol, , and - Mad Dukol, Norleha; Mohamed Sally, Azlaini; Jamaludin, Rosmawati; Nik Ali, Nik Abibahton (Universiti Teknologi MARA, Perak, 2020)
Organic chemistry is a challenging subject for students as there are many terms, symbols and processes involved in understanding the subject. A specialised learning tool is needed to facilitate learning and scaffold student understanding. Fan_TESTick kit, a colour-coded hand fan made from everyday material is one such tool. It allows students, teachers and users to make quick references on organic chemistry tests, observations and equations. A usage study which involved 22 students was conducted. Pre and post-tests and questionnaires were used to collect data. The students' average pretest score was 16% whereas after the toolkit was introduced, the posttest score increased to 87%. Results obtained from a questionnaire found that 100% of the students agree that the use of this kit brings various positive effects towards their learning and understanding on chemical tests. From the answer of the open-ended questions of 21 students, 18 gave positive feedback, 1 gave neutral, 2 no feedback at all and no negative feedback. From the pretest, posttest and questionnaire analysis, we concluded that Fan_TESTick kit is a powerful learning tool in assisting students to understand and memorize chemical tests related to organic compounds. This toolkit is userfriendly in terms of its size, lightness, compactness and portability.